Access to Allene‐Containing Molecules via Enantioselective Reactions of Azolium Cumulenolate Intermediates. (24th May 2021) - Xie, Yongtao; Yang, Xing; Xu, Jun; Chai, Huifang; Liu, Hongxia; Zhang, Junmin; Song, Jun; Gao, Yuan; Jin, Zhichao; Chi, Yonggui Robin
Abstract: Azolium cumulenolates are a special type of intermediates in N‐heterocyclic carbene catalysis. They contain elongated linear structures with three contiguous C=C bonds and sterically unhindered α‐carbon atoms. These structural features make it difficult to develop enantioselective reactions for these intermediates. Here we disclose the first carbene‐catalyzed highly enantioselective addition reactions of azolium cumulenolates. The reaction starts with alkynals as the precursors for azolium cumulenolate intermediates that undergo enantioselective addition to activated ketones. From the same set of substrates, both allene and spirooxindole products can be obtained with high yields and excellent enantioselectivities. The allene moieties in our optically enriched products carry rich reactivities and can be transformed to diverse molecules. The spirooxindole scaffolds in our products are important structural motifs in natural products and medicines. Abstract : The first carbene‐catalyzed highly enantioselective addition involving cumulenolates is disclosed. Both allene and spirooxindole products could be accessed with high yields and excellent enantioselectivities by varying the amount of the base.